OBESITY, LEFT VENTRICULAR REMODELING, AND 24-HOUR BLOOD PRESSURE PROFILE IN MILITARY PERSONNEL WITH ARTERIAL HYPERTENSION: A CONTEMPORARY CLINICAL ASSESSMENT - Salikhov B.R; Alyavi A.L (TADQIQOTLAR, 2025)
Abstract Background. Obesity is a major modifiable risk factor for cardiovascular disease and strongly contributes to the development of hypertension and left ventricular (LV) remodeling. Military personnel represent a unique population with high cardiometabolic risk due to occupational stress and lifestyle patterns. Objective. To investigate the relationship between body mass index (BMI), LV structural remodeling, and circadian blood pressure (BP) profile in hypertensive servicemen.